Reinforcing Religious Moderation through Local Culture-Based Pesantren - Muhammad Alqadri Burga; Muljono Damopolii (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
The study aims to explore the diversity of pesantren (Islamic boarding schools) in Soppeng Regency, Indonesia. The regency is known as a place for multicultural education based on local culture which is expected to strengthen religious moderation. This research is qualitative with a phenomenological approach. The object is selected purposively; four pesantren institutions in Soppeng Regency, Yasrib (Nahdhatul Ulama), Muhammadiyah Lajoa, Al-Irsyad (Darud Da'wah wal Irsyad) Pattojo, and Al-Ihsan Appanang (Jamaah Tablig). The results of the study show that the diversity of pesantren serves as a place for multicultural education. Pesantren may reflect the diversity of society, founding organizations, institutional typologies, and networks. The local culture-based pesantren is designed to promote multicultural education model which was developed by applying several local culture values: sipakatau (mutual respect), sigunakannge' (reminding each other), sipakalebbi (mutual glorification), and sipammase-mase (mutual love). Those values are used as the principles of multiculturalism which is carried out with the ethos of siri (respect themselves) in the life of the pesantren community. Multicultural education model strengthens the principle of wasaṭiyah (moderate) religious moderation through the ideology of Ahl al-Sunnah wa al-Jamā'ah. Religious moderation facilitates the society to accommodate local culture, express strong national commitments, and grow tolerance in the spirit of egalitarianism.